[Rezension von: A.G. Röber, Hopes for better spouses: protestant marriage and church renewal in early modern Europe, India, and North America] - Stievermann, Jan (Journal of American history, 2014)
This is a fascinating in-depth study of how marriage developed as a theological concept and practice within the Lutheran tradition. The focus is on the varietie
Gesehen am 13.08.2020
Keywords: Rezension